2020
DOI: 10.1371/journal.pone.0237001
|View full text |Cite
|
Sign up to set email alerts
|

Highs and lows: Genetic susceptibility to daily events

Abstract: Why people differ in their susceptibility to external events is essential to our understanding of personality, human development, and mental disorders. Genes explain a substantial portion of these differences. Specifically, genes influencing the serotonin system are hypothesized to be differential susceptibility factors, determining a person's reactivity to both positive and negative environments. We tested whether genetic variation in the serotonin transporter (5-HTTLPR) is a differential susceptibility facto… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Interestingly, two previous genotyping studies in motor-FND found i) that serotonin receptor gene polymorphism was related to symptom severity, childhood abuse burden, and functional amygdala -middle frontal gyrus connectivity, and ii) an increased methylation of the oxytocin receptor gene [42,43]. Overall, genetic variations in serotonin and oxytocin receptor systems have been related to amygdala reactivity, acute stress responses, and affective vulnerabilities to everyday events [4,6,[85][86][87][88][89]. Type and severity of stressors has been shown to differentially influence regionspecific serotonin receptor gene expression (e.g., chronic psychosocial stress reduced expression in cingulo-insular and hippocampal regions [90]), further corroborating the importance of ALE subtyping [91].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, two previous genotyping studies in motor-FND found i) that serotonin receptor gene polymorphism was related to symptom severity, childhood abuse burden, and functional amygdala -middle frontal gyrus connectivity, and ii) an increased methylation of the oxytocin receptor gene [42,43]. Overall, genetic variations in serotonin and oxytocin receptor systems have been related to amygdala reactivity, acute stress responses, and affective vulnerabilities to everyday events [4,6,[85][86][87][88][89]. Type and severity of stressors has been shown to differentially influence regionspecific serotonin receptor gene expression (e.g., chronic psychosocial stress reduced expression in cingulo-insular and hippocampal regions [90]), further corroborating the importance of ALE subtyping [91].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we observed that naturalistic everyday life stressors are associated not only with higher negative affect, but also lower positive affect (Sicorello, Dieckmann, et al, 2020). Therefore, we included additional analyses on neural signatures for positive emotions as well.…”
Section: Introductionmentioning
confidence: 92%
“…They further monitored circumstances associated with observed variations. Sicorello et al (2020) were able to show that the participants’ susceptibility to external events was shaped by variation in the serotonin transporter gene. Vice versa, EMA allows stress researchers to systematically track fluctuations in individual stress levels along a specific stressful event (event-based monitoring) ( Shiffman et al, 2008 ).…”
Section: Perspectives For Stress Research During the Current Covid-19 Pandemicmentioning
confidence: 98%
“…With regard to stress research, EMA is capable of registering random fluctuations in individual stress levels at (random or fixed) time intervals ( Kudielka et al, 2012 ; Schlotz, 2011 ; Shiffman et al, 2008 ). Sicorello et al (2020) , for example, asked their participants over several days to complete stress-related questionnaires on their smartphones. They further monitored circumstances associated with observed variations.…”
Section: Perspectives For Stress Research During the Current Covid-19 Pandemicmentioning
confidence: 99%